Comparison of contact force control strategies on different robot arm types - (:unkn) unknown (My University, 2010)
Nowadays robots are used in various areas. There are extremely important applications where the robot arm tip comes in contact with the environment or an object. During controlling an object, static or in motion, the object or the robot arm should not be damaged. The interaction forces are important in such conditions. Whether the task succeeds or fails depends on how accurate the interaction forces are controlled. The interaction forces are changed depending on the motion of the robot arm. Therefore, to control interaction forces a force control algorithm must be developed. In this research a force control algorithm will first be developed for the quasi-static contact tasks, then it will be extended to the dynamic cases. The goal of this study is to compare force control strategies to achieve the desired interaction forces between the robot arm tip (end-effector) and the environment during contact tasks. Taguchi L9 method is used for comparison of selected force control algorithms which are modeled in SIMULINK MATLAB program. © 2010 by ASME.